A rare case of unruptured viable secondary ovarian pregnancy after IVF/ICSI treated by conservative laparoscopic surgery - Bharti Dhorepatil; Aarti Rapol (Wolters Kluwer Medknow Publications, 2012)
Although the incidence of ectopic pregnancy is on the rise, ovarian pregnancy after in vitro fertilization and embryo transfer is a rare entity. Here, we report a case of unruptured ovarian pregnancy following in-vitro fertilization/intracytoplasmic sperm injection, which was treated by conservative laparoscopic surgery.